Literatur Review Artikel : Metode Spektrofotometri Inframerah Sebagai Penetapan Kadar Obat Pada Sediaan Farmasi - Nur Lestriyani; Mutiara Aulia Putri; Nurul Khotimah; Raka Puja Susanto (Pusat Riset dan Inovasi Nasional, 2025)
In the field of pharmacy, infrared spectrophotometry, particularly Fourier Transform Infrared (FTIR), has become an important analytical method, especially for determining the content of active substances in drug preparations. This method has many advantages, including rapid analysis, high precision, and non-destructive characteristics, as well as the ability to identify specific functional groups in chemical compounds. Based on a review of ten recent scientific articlesThe aim of this study is to provide an overview and analyze the use of the FTIR method in determining the drug content. The research results demonstrate that FTIR consistently provides results that meet the standards of the Indonesian Pharmacopoeia, with an accuracy above 99% and a precision (RSD) below 1%. Moreover, this method is highly reliable for analyzing various drug compounds, ranging from analgesics and antibiotics to other complex compounds, due to the high sensitivity indicated by the LOD and LOQ parameters. The FTIR method is also very useful in analysis.